Evaluating Apps for Learning and Teaching - Jonas-Dwyer, Diana Renee D; Clark, Catherine; Celenza, Anthony; Siddiqui, Zarrin S (International Journal of Emerging Technologies in Learning (iJET), 2012)
A growing number of educators and students are adopting mobile devices and using applications (apps). There are often no formal guidelines to assist with evaluating apps. A review of the literature was conducted to determine relevant criteria that could be applied to evaluating apps. Relevant examples are included where appropriate. Evaluation criteria are offered to assist educators and students with determining the suitability of apps.